The Effect of Magnesium on Retinal Venous Pressure of Patients with Normal-Tension Glaucoma and Flammer Syndrome - Rainer Gruber; Issa Fetian; Lei Fang; Fabio Valeri; Karl-Georg Schmidt; Maneli Mozaffarieh (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
# Purpose